A High Power Quality Buck-H Auxiliary Power Converter in Railway Applications - Lan, Zheng; Wu, Fangreng; He, Dong; Yu, Xueping; Zeng, Jinhui; Xiao, Fan (Frontiers in Energy Research, 2022)
DC voltage utilization and AC voltage harmonics are important evaluation indexes for Auxiliary Power Converter in Railway Applications. To improve the above two indicators, a novel switch-mode modulation method and quasi-PR control strategy for Buck-H three-phase inverter is proposed in this paper. The Buck-H three-phase inverter integrates the AC side filter circuit into the DC Buck circuit, which reduces the volume of the filter capacitor and improves the filtering effect. This novel switch-mode modulation method uses only one high frequency switch per phase, which reduces the switching losses and thereby increases overall efficiency. In addition, this switch-mode modulation absence of shoot-through menace eliminates the dead time requirement. Meanwhile, the quasi-proportional-resonance (PR) controller and its control parameters are optimized to improve the AC voltage tracking performance. The influence of PR control parameters on system performance is analyzed in detail. The proposed switch-mode modulation method and control method can effectively reduce the harmonic distortion rate of the system. The effectiveness is verified through the StarSim hardware-in-the-loop experimental results.